LEGAL, INNOVATIVE AND SCIENTIFIC APPROACHES TO STUDY MODERN DIGITAL BANKING (International scientific-electronic journal “Pioneering studies and theories”, 2025)
Banking system, from its origin to these days, have undergone many changes including legal intervenes, technological implementations, innovations resulting in scientific disputes. The research paper examines terminology including direct bank, home bank, online bank, e-bank, virtual bank, digital bank, neo-bank studied by different methods in literature. Moreover, this article scrutinizes legal, technological and chronologic approaches to research bank industry, in order to find future tendencies in the field. Furthermore, the digital transformation of banking sector of Uzbekistan has been analyzed in this paper, underlining study questions for future research.